Alterations in physiological and biochemical characteristics of Prunus sibirica seedlings raised from spaceflight seeds - Ying Kang; Yuncheng Zhang; Jianhua Chen; Qingfu Yu; Biao Li; Yijin Wang; Shengjun Dong (PLoS ONE, 2025)
The aim was to explore the alterations in growth traits, physiological and biochemical characteristics of Prunus sibirica seedlings raised from spaceflight seeds. The seedlings cultivated by the “Shenzhou XII” spacecraft carrying the seeds of superior clones of P. sibirica were used to observe their growth traits and determine physiological indicators. The results showed that plant height of Prunus sibirica seedlings raised from spaceflight seeds increased by 18–34% and internode length increased by 8–26%, but the number of primary branches, secondary branches, and leaves showed no significant change compared to the ground control. Leaf length and width of Prunus sibirica seedlings raised from spaceflight seeds were significantly higher than those of the ground control, with leaf length, width, and area increasing to 1.21–1.80 times higher than that of the ground control. Furthermore, the antioxidant and osmoregulatory capacities of P. sibirica seedlings raised from spaceflight seeds were altered. The peroxidase (POD) activity and Malondialdehyde (MDA) content were increased in ST28, ST207, and ST507, while they were reduced in ST1 and ST453. Compared with the ground control, the content of soluble sugar(SS), starch (St), and free proline (Pro) were significantly or highly significantly increased in all lines. The content of soluble protein (SP) was significantly increased in ST1, ST28, ST207, and ST507, while there was no significant change in ST453. P. sibirica seedlings raised from spaceflight seeds exhibited increased leaf pigment content, the interstitial CO2 concentration (Ci), net photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr). In conclusion, compared with the ground control, the growth indexes and physiological characteristics of Prunus sibirica seedlings raised from spaceflight seeds were changed, and the direction of change was different for different lines. This provided a foundation for subsequent germplasm improvement and variety selection.